REV-ERBα integrates colon clock with experimental colitis through regulation of NF-κB/NLRP3 axis. Issue 1 (December 2018) - Wang, Shuai; Lin, Yanke; Yuan, Xue; Li, Feng; Guo, Lianxia; Wu, Baojian
Abstract The roles of Rev-erbα and circadian clock in colonic inflammation remain unclarified. Here we show colon clock genes (includingRev-erbα ) are dysregulated in mice with DSS-induced colitis. In turn, disruption of the circadian clock exacerbates experimental colitis. Rev-erbα-deficient mice are more sensitive to DSS-induced colitis, supporting a critical role of Rev-erbα in disease development. Further, Rev-erbα ablation causes activation of Nlrp3 inflammasome in mice. Cell-based experiments reveal Rev-erbα inactivates Nlrp3 inflammasome mainly at the priming stage. Rev-erbα directly represses Nlrp3 transcription through specific binding to the promoter region. Additionally, Rev-erbα represses p65 transcription and indirectly repressed Nlrp3 via the NF-κB pathway. Interestingly, Rev-erbα activation in wild-type mice by SR9009 attenuates DSS-induced colitis, whereas the protective effects are lost inNlrp3 −/− andRev-erbα −/− mice. Taken together, Rev-erbα regulates experimental colitis through its repressive action on the NF-κB/Nlrp3 axis. Targeting Rev-erbα may represent a promising approach for prevention and management of colitis. REV-ERBα is a nuclear receptor that links the circadian pathways with those of metabolism. Here the authors show REV-ERBα is also involved with linking the circadian system with the inflammatory pathways of an experimental model of colitis through regulation of the NF-κB/NLRP3 axis.